Impact of export duty structure on the performance of Malaysian palm oil industry - Wong, Kelly Kai Seng (2014)
The loss of market shares in palm oil production and even in the amount of exports has given a wake-up call to the Malaysian palm oil industry to strengthen competency and competitiveness in the global market, especially in the perspective of export and local received prices. The key policy instrument to influence these two prices in Malaysia and Indonesia is the value of export duty which is a price gap between the export price and the local producer‟s received price of palm oil. In 2013, the Malaysian government followed the footsteps of the world top palm oil producer; Indonesia, by restructuring the export tax on CPO, i.e. the reduction of its rate within the range of 4.5% to 8.5% and increase the minimum threshold price from the previous RM 650 per tonne to current RM 2,250 per tonne. Due to the fact that the threshold prices have hugely increased, the export duty taxed by the Malaysian government in the first two months of the year 2013 is zero value and not more than RM 130 per tonne for the months following. The ultimate objective of the reduction of export tax was to enhance the local production as well as to encourage the export of local palm oil. Nonetheless, after executing this policy, several questions have arisen. These are whether this new taxation structure could enable the Malaysian palm oil industry to sustain in the competitive global market in the long run, whether the rates of reductions in the new revised export duty structure could have a similar effect on the increment of threshold prices, whether the export duty trap could occur in the Malaysian current export duty structure, and finally what would be the consequences for the Malaysian palm oil industry if the Indonesian government revised its export duty structure and further reduced its export duty on CPO. Motivated by the significance of this export duty policy on the performance of the Malaysian palm oil industry, the main objective of this study is to investigate the impact of export duty structure change in Malaysia and Indonesia on the performance of the Malaysia palm oil industry. In a nutshell, this study is divided into three major divisions in order to provide a comprehensive and robust overview regarding the impact of the export duty. The first division is to construct a Malaysian palm oil commodity model which is analyzed by 28 behavioural estimated equations through the times series econometric approach (AutoRegressive Distrubuted Lag) and then combined with the 11 identity equations. Through the comprehensive robustness and validation tests, the palm oil model confirms the credibility of the forecasted values. In this first objective, the simulation forecast results show the new structure of export duty on Malaysian CPO reduces the gap between the local received and export prices. Through an increase of received price and a decrease of export price, the performance of the Malaysian palm oil industry could sustain its steady growth over the next decade. Hence, this new structure can be maintained to enhance the local producer‟s competitive power if there is no further Indonesian export duty reduction policy revisions in the future. The second division of this study examines the impact of the abatement of the Malaysian palm oil export duty on the local palm oil industry performance. The simulation results show that the impact of reductions in the export duty rates and the impact of increases in the threshold prices on Malaysian palm oil industry have the same impact but with a different magnitude. Even thought, the simulated results indicate that the policy of further reductions in Malaysian export duty will promote its positive effects on the local palm oil industry; however, the impact is shown as to not be significant. Thus, the further reduction of export tax is believed to no longer be the most effective policy in enhancing the competitiveness of local palm oil industry in the future. The main justifications of this statement are the low export tax introduced and the tax being levied is too low. This has created a condition similar to trade liberalization but in practice, this undesirable condition is known as the export duty trap. In this situation the current amplitude of reducing the Malaysian export tax is very constrained. Therefore, policymakers have to be aware of the possibility that the reduction of export tax may no longer be an effective approach in facilitating the development of palm oil industry. The findings from the third objective indicate that the reduction of the Indonesian export duty on palm oil would cause a negative impact on the Malaysian export supply. This reflects that the export duty policy of Indonesia – the closest competitor of Malaysia, has an undeniably close relationship with the Malaysian palm oil industry performance, especially in the Malaysian demand market. The abatement of the Indonesian export duty has led to the shrinking of Malaysian palm oil market share in the global market. This significantly reduces the global excess demand for the Malaysian palm oil and the reduction of the Indonesian export levy would drive the export price even lower. Correspondingly, the global excess demand would shift towards the Indonesian palm oil market due to its reduced price. The shift of the global excess demand out of Malaysia would lead to a palm oil export deflation. As a consequence, the world price of palm oil as well as the Malaysian palm oil export price will drop. In conclusion, the overall findings suggest that if there are no Indonesian export duty reduction policy revisions in the future, the policymakers can maintain the current export duty structure of the Malaysian CPO in order to achieve a sustainable growth. In contrast, the policymakers have to recognize that the export tax reduction policy is no longer regarded as the most effective policy in enhancing the competitiveness of the local palm oil industry, if the Indonesian government revises and reduces its export duty through such means as lowering the export tax rates and increasing the threshold prices. The Malaysian local producers have to be more independent and need to diversify their palm oil products through some innovative schemes as well as R&D. As an open trade market, the blue ocean strategy seems like an unavoidable strategy for the Malaysian palm oil industry in which the local producers should create new market demands for their palm oil products rather than compete head-to-head with other global palm oil producers, especially Indonesia.